Adapting the Pregnancy Physical Activity Questionnaire for Japanese Pregnant Women. Issue 1 (19th December 2013) - Matsuzaki, Masayo; Haruna, Megumi; Nakayama, Kae; Shiraishi, Mie; Ota, Erika; Murayama, Ryoko; Murashima, Sachiyo; Yeo, SeonAe
ABSTRACT Objective To assess the psychometric properties of the Pregnancy Physical Activity Questionnaire (PPAQ) for women who read and speak Japanese. Design This longitudinal study used a self‐report questionnaire and quantitative biometric and instrumental measurements (actigraph) to assess the reliability and criterion validity. Setting A university hospital in Tokyo, Japan. Participants Sixty‐nine pregnant women living in Tokyo and its suburbs were recruited. Methods The test–retest reliability of the Japanese version of the Pregnancy Physical Activity Questionnaire (PPAQ‐J) was evaluated through intraclass correlation coefficients (ICCs) between PPAQ‐J results administered three times (at recruitment, 7 and 14 days later). Criterion validity was assessed by comparing results to actigraph measures using Spearman's correlation coefficients. Participants wore the actigraph over the 2‐week research period. Data from 58 participants were analyzed for test–retest reliability. The data of 54 participants were used to analyze criterion validity. Results The ICCs for the first and second and for the first and third PPAQ‐J questionnaires were ≥0.56 for total activity and activities broken down by intensity and type (in metabolic equivalents [METs] × hours/day). To evaluate criterion validity, Spearman's correlation coefficients were calculated between the first measurement of the PPAQ‐J and three published cut‐points used to classify actigraph data (minutes/day); correlations ranged from .02 to .35 for total activity, −.21 to −.25 for vigorous activity, −.09 to .38 for moderate activity, and .01 to .28 for light activity. Conclusion The PPAQ‐J is a psychometrically sound and comprehensive measure of physical activity in pregnant Japanese women.